Differentiating Neuropathic and Inflammatory Heel Pain: Clinical Evaluation and Diagnostic Utility of the Sural Nerve Ankle Block - Tailor, Dhaval M; P N Kulkarni (International Journal of Medical Research, 2024)
Background: Heel pain is a prevalent issue with diverse aetiologies, including neuropathic and inflammatory causes, each requiring different therapeutic approaches. This study aims to differentiate between these types of heel pain using clinical evaluation and the sural nerve ankle block as a diagnostic tool. Methods: This prospective analytical study was conducted in the Department of Orthopaedics at Krishna Institute of Medical Sciences, Karad, India, over an 18-month period. A total of 50 patients aged 18 years and above presenting with heel pain were included. After obtaining informed consent, patients underwent clinical assessment, including palpation, Windlass test, Gore’s sign, and Visual Analogue Scale (VAS) scoring. A sural nerve block was administered to assess its diagnostic value, and VAS scores were recorded immediately and at various follow-up intervals. Results: Neuropathic pain was characterized by burning sensations, persistence throughout the day, unilateral distribution, and positive Gore’s sign, whereas inflammatory pain showed sharp morning pain, bilateral distribution, and positive Windlass test. Immediately post-block, neuropathic pain patients showed significant pain reduction, which persisted over time, while inflammatory pain patients exhibited minimal improvement. The sural nerve block proved effective in diagnosing neuropathic pain. Conclusion: Clinical assessment combined with the sural nerve block can effectively distinguish neuropathic from inflammatory heel pain. Neuropathic pain patients experienced significant relief post-block, confirming its utility as both a diagnostic and therapeutic tool in neuropathic cases.